Development and Evaluation of Novel Ethosomal Vesicular Drug Delivery System of Sesamum indicum L. Seed Extract - Somwanshi, Sachin B. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the present research work is to prepare ethosome of Sesamum indicum L. seed extract, its incorporation into gel formulations and to characterize the developed ethosomes and gel formulations using various parameters. Methods: Different formulations of ethosomes using phospholipids (1–4%) and ethanol (10–40%) were prepared using S. indicum L. seed extract by solvent dispersion technique and were characterized. Carbopol 934 was used to prepare ethosomal gel. Results: The size of ethosomes was found to be in the range of 139.7 ± 10.55–231.8 ± 12.43 nm while polydispersity index ranges from 0.114 to 0.348 and ZP were between −17.0 and 47.7 mV. Morphology studies showed smooth surface under phase contrast microscope showed, transmission electron microscope showed unilamellar nature with near spherical shape. The EE of ethosomes was found to be in the range of 82.12 ± 1.88% and 97.26 ± 0.65%. Ethosomes were further added to Carbopol 934 for gel formation, and subsequently, evaluated for their physicochemical properties. The pH of the gel formulations was found to be in the range of 5.97 ± 0.01–6.22 ± 0.02. Viscosities of gels were ranging between 6080 and 119200 centipoises at 25 rpm. In vitro diffusion study was conducted for ethosomes incorporated in viscous gel. Conclusions: The present study revealed that ethosomal vesicular delivery system of seeds extract of S. indicum L. is an encouraging novel approach for herbal extract.